From Nacionalista Anti-Kabbalistic Polemic to Aryan Kabbalah in the Southern Cone. - Brown, Jeremy Phillip (Journal of Religion, 2019)
The article discusses the adoption of kabbalistic discourses by the far-right political figures Julio Meinvielle and Miguel Serrano Fernández in Argentina and Chile, respectively. Topics include esoteric ideas promoted by Serrano, neo-Nazi aspects of Serrano's thought in relation to his interpretation of Judaism, and the notion of heresy in Meinvielle's thought.